2011
DOI: 10.1098/rspb.2011.1294
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition strategy as a means of local adaptation to plant defence in native and invasive populations of the viburnum leaf beetle

Abstract: Herbivores have been hypothesized to adapt locally to variation in plant defences and such adaptation could facilitate novel associations in the context of biological invasions. Here, we show that in the native range of the viburnum leaf beetle (VLB, Pyrrhalta viburni ), two populations of geographically isolated hostsViburnum opulus and Viburnum tinus-have divergent defences against VLB oviposition: negative versus positive density-dependent egg-crushing wound responses, respectively. Populations of beetles c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(48 reference statements)
1
10
1
1
Order By: Relevance
“…Second, the oviposition choices and strategies of VLB appear to be shaped, at least in part, by this wound response. Not only have we shown here that VLB prefers undefended dead twigs, but also we have previously shown that native populations of VLB have locally adapted to plant species with differential twig defensive responses (Desurmont et al 2012). Nonetheless, in the majority of Viburnum species, we observed wound responses that were dramatically lower under natural conditions (i.e., where beetles had a choice for oviposition) as compared to the results of a manipulative study, where VLB females were forced to oviposit on particular branches, especially at high egg density (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Second, the oviposition choices and strategies of VLB appear to be shaped, at least in part, by this wound response. Not only have we shown here that VLB prefers undefended dead twigs, but also we have previously shown that native populations of VLB have locally adapted to plant species with differential twig defensive responses (Desurmont et al 2012). Nonetheless, in the majority of Viburnum species, we observed wound responses that were dramatically lower under natural conditions (i.e., where beetles had a choice for oviposition) as compared to the results of a manipulative study, where VLB females were forced to oviposit on particular branches, especially at high egg density (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…The production of scar tissue in response to oviposition is lower in North American Viburnum species than in Eurasian congeners and this lower response may have contributed to VLB invasion in North America (Desurmont et al , 2012. However, our field observations show that neither variation in twig defense nor insect performance explained VLB defoliation patterns.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Heavily infested twigs often die, circumventing their capacity to produce a wound response, and egg survivorship is consequently positively associated with egg mass density. This correlation was consistent across 16 Viburnum species from Europe, Asia, and North America , with the exception of V. tinus, a European species (Desurmont et al, 2012). Here, we explore two potential additional benefits of aggregative oviposition.…”
Section: Introductionmentioning
confidence: 55%
“…These studies include the deposition of eggs either on or in plant tissues of closely related taxa (Müller & Rosenberger, 2006;Gültekin, 2007), the triggering of gall induction at oviposition sites (Formiga et al, 2011), and the ovipositor probing of egg-insertion sites to assess plant-tissue suitability by agromyzid leaf miners (Sehgal, 1971;Winkler et al, 2010). In addition, insect oviposition frequently activates counterdefenses by the host plant that include chemical defenses such as the generation of plant-host volatile chemicals as a response from oviposition lesions that attract egg parasitoids (Colazza et al, 2004;Moraes et al, 2008), and structural defenses such as egg-crushing wound response tissue from the plant hosts of certain leaf beetles (Desurmont et al, 2012). The natural history of insect oviposition in plants has provided a major source of data and inferences as to how plants and insects interact on modern ecological and evolutionary time scales (Renwick, 1989;Childers, 1997).…”
Section: Introductionmentioning
confidence: 99%